Anti-additive precipitation packaging film and preparation method thereof, photovoltaic module
The additive is coated through O/W emulsification method and blended with POE particles. The high melting point and low melting point polymer wall materials control the release of additives, which solves the problem of easy precipitation of POE film additives and improves the film The degree of cross-linking and peeling force extend the service life.
Patent Information
- Application Number
- CN202310738569.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-06-21
AI Technical Summary
During the preparation process, additives are prone to precipitation, resulting in low curing cross-linking and degradation of adhesion, which affects performance.
Microcapsules are prepared by coating additives with O/W emulsification method and blended with POE particles. The release of additives is controlled under casting and lamination temperature by combining high melting and low melting point polymer walls to prevent auxiliary agents. The agent precipitates.
It effectively improves the crosslinking degree of the adhesive film, reduces the precipitation of additives, improves the initial crosslinking degree and peeling force of the POE adhesive film, and extends the service life.
Smart Images

Figure CN116948560B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of packaging adhesive films, and in particular relates to an anti-precipitation packaging adhesive film and a preparation method thereof, and a photovoltaic module. Background Art
[0002] Solar photovoltaic technology is a technology that converts solar energy into electricity. Its main component is a semiconductor material that can release electrons. There are two layers of semiconductors in solar photovoltaic cells, the positive electrode and the negative electrode. When sunlight shines on the semiconductor, the two electrodes will generate current. Solar photovoltaic systems not only operate under strong sunlight, but can also generate electricity on cloudy days. The most important component of a solar cell is the solar cell chip. The cell chip is brittle and thin, and it is easy to break and fail. If it is directly exposed to the air for a long time, the photoelectric conversion efficiency of the cell chip will be attenuated due to rain, moisture, dust, etc. In order to ensure that the service life of the solar cell is more than 25 years, it is necessary to protect it through lamination, glue sealing and other methods without affecting the working performance of the cell chip, so that it can form a usable solar cell power generation device, generally called a photovoltaic module.
[0003] The lamination packaging process can realize the packaging of solar cell modules for large-scale industrial production. The packaging technology is widely used in the preparation of photovoltaic modules, and the packaging film is indispensable. The packaging film encapsulates the welded battery chip and then bonds it to the back plate and the protective material cover. The main materials of the film include polyvinyl butyral (PVB), ethylene-vinyl acetate copolymer (EVA), thermoplastic polyurethane (TPU), silicone resin (Silicone), thermoplastic polyolefin (TPO) and polyolefin elastomer (POE).
[0004] As a rising star in the field of solar cell encapsulation film, POE has become a good substitute for traditional EVA film due to its excellent processing performance, optical properties and weather resistance. However, due to the characteristics of POE particles themselves, especially the low surface polarity different from EVA, it is easy for additives to precipitate during the preparation of POE film. As a result, the curing and cross-linking degree of POE film is low, the adhesion is reduced, and the performance is affected. The precipitated additives adhere to the surface of the film, causing slippage and affecting production. How to solve this problem is of great practical application value. Summary of the invention
[0005] The invention provides an anti-additive precipitation encapsulation adhesive film and a preparation method thereof, and a photovoltaic module, so as to solve the problem that the additive in the POE adhesive film is easy to precipitate.
[0006] In order to solve the above technical problems, the present invention provides a method for preparing an anti-additive precipitation encapsulation film, comprising the following steps: step S1, coating the additives required for the film by an O / W emulsification method to prepare microcapsules; step S2, blending the microcapsules with POE particles, and casting the film to obtain an anti-additive precipitation encapsulation film; wherein the O / W emulsification method of the microcapsules includes: dissolving a composite polymer wall material in water to prepare an aqueous solution with a mass fraction of 10 to 40wt%, adding the additive to the aqueous solution for high shear emulsification, high-speed dispersing and homogenizing emulsification at 5000 to 15000 rpm for 3 to 10 minutes, and curing to obtain the microcapsules; and the composite polymer wall material is a combination of a low-melting-point polymer wall material with a melting point not higher than 100°C and a high-melting-point polymer wall material with a melting point not lower than 110°C.
[0007] In a second aspect, the present invention further provides an anti-auxiliary agent precipitation encapsulation film obtained by the preparation method as described above, comprising: microcapsules; wherein the microcapsules are prepared by coating the auxiliary agent in an O / W type emulsification manner.
[0008] In a third aspect, the present invention further provides a photovoltaic module, comprising the anti-adjuvant precipitation packaging film as described above.
[0009] The beneficial effects of the present invention are that the anti-additive precipitation encapsulation adhesive film and its preparation method, and the photovoltaic module of the present invention encapsulate the additive in the microcapsule by selecting a high melting point and a low melting point polymer wall material, so that the low melting point polymer wall material releases part of the additive at the casting temperature and can keep the skeleton intact, and at the lamination temperature, the low melting point polymer wall material is completely melted and the high melting point polymer wall material is softened and deformed, so that the additive is completely released without precipitation, thereby effectively achieving the purpose of providing the cross-linking degree of the film.
[0010] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practicing the present invention.
[0011] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0013] Figure 1This is a diagram showing the microscopic morphology changes of the microcapsules of the present invention before and after being heated;
[0014] Figure 2 It is a diagram showing the change in internal morphology of the adhesive film of the present invention before and after lamination. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] The invention provides a method for preparing an anti-additive precipitation encapsulation film, comprising the following steps: step S1, coating the additives required for the film by an O / W emulsification method to prepare microcapsules; step S2, blending the microcapsules with POE particles, and casting the film to obtain the anti-additive precipitation encapsulation film; wherein the O / W emulsification method of the microcapsules comprises: dissolving a composite polymer wall material in water to prepare an aqueous solution with a mass fraction of 10 to 40wt%, adding the additive into the aqueous solution for high shear emulsification, high-speed dispersing and homogenizing emulsification at 5000 to 15000 rpm for 3 to 10 minutes, and curing to obtain the microcapsules; and the composite polymer wall material is a combination of a low-melting-point polymer wall material with a melting point not higher than 100°C and a high-melting-point polymer wall material with a melting point not lower than 110°C.
[0017] In this embodiment, specifically, the composite polymer wall material is a combination of gelatin and gum arabic, or any one of a combination of chitosan and cyclodextrin, wherein the melting point of gelatin is about 50°C, the melting point of chitosan is about 70°C, which are lower than the casting processing temperature, the melting point of gum arabic is about 150°C, and the melting point of cyclodextrin is about 250°C, which is higher than the lamination temperature.
[0018] In this embodiment, specifically, the mass ratio of the low melting point polymer wall material to the high melting point polymer wall material is 1:9 to 3:7.
[0019] In this embodiment, specifically, the mass ratio of the composite polymer wall material to the auxiliary agent is 3 to 10:1.
[0020] In this embodiment, specifically, the solidification is a composite coagulation method, the emulsified system is heated to 50-60°C, the pH value of the system is adjusted to 3 with acetic acid, coagulated for 30-60 minutes, cooled to 15-20°C in an ice water bath, and then the pH value of the system is adjusted to 6 with ammonia water, glutamine aminotransferase is added, the temperature is maintained at 500-2500rpm and stirred for solidification for 2-4h, the mixture is allowed to stand, layered, centrifuged, and dried. Preferably, the mass fraction of glutamine aminotransferase is 0.1-1% of the solid content of the mixture.
[0021] In this embodiment, specifically, the auxiliary agents include a cross-linking agent, a co-cross-linking agent, a light stabilizer, an antioxidant and a silane coupling agent.
[0022] In this embodiment, specifically, the cross-linking agent is any one of dibenzoyl peroxide, diisopropylbenzene peroxide, tert-butyl peroxide 2-ethylhexyl carbonate, 1,1-di-tert-butyl peroxide cyclohexane, tert-amyl peroxide 2-ethylhexyl carbonate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, di(4-methylbenzoyl) peroxide and tert-butyl peroxide-3,5,5-trimethylhexanoate, or a mixture of at least two thereof.
[0023] In this embodiment, specifically, the auxiliary cross-linking agent is any one of ethoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane triacrylate, triallyl isocyanurate, and triallyl cyanurate, or a mixture of at least two thereof.
[0024] In this embodiment, specifically, the light stabilizer is any one of a light shielding agent light stabilizer, a quencher light stabilizer, a free radical scavenger light stabilizer and a hydroperoxide decomposer light stabilizer, or a mixture of at least two of them.
[0025] In this embodiment, specifically, the antioxidant is any one of a hindered phenol antioxidant, an aromatic amine antioxidant, a phosphite antioxidant, a thioether antioxidant and a metal passivator antioxidant, or a mixture of at least two thereof.
[0026] In this embodiment, specifically, the silane coupling agent is any one of a vinyl silane coupling agent, a chloroalkyl silane coupling agent, an aminoalkyl silane coupling agent, an epoxyalkyl silane coupling agent, a methacryloxyalkyl silane coupling agent, a sulfur-containing hydrocarbon silane coupling agent, a pseudohalogen silane coupling agent or a quaternary aminoalkyl silane coupling agent, or a mixture of at least two thereof.
[0027] In this embodiment, specifically, the method for preparing microcapsules using chitosan and cyclodextrin as polymer wall materials and coating auxiliary agents is as follows: chitosan and cyclodextrin are dissolved in water, heated to obtain a mixture solution, and maintained at a constant temperature; then the auxiliary agent is added to the aqueous solution for high shear emulsification, and then solidified to obtain microcapsules coated with the auxiliary agent.
[0028] In this embodiment, preferably, the mass ratio of chitosan to cyclodextrin is 1:9, 2:8 and 3:7.
[0029] In this embodiment, preferably, the mass ratio of the polymer wall material to the additive is 4:1.
[0030] In this embodiment, preferably, the temperature is 70°C, 75°C and 80°C.
[0031] In this embodiment, preferably, the solid content of the prepared mixture solution is 10%, 20%, 30% and 40% by mass.
[0032] In this embodiment, preferably, the shearing speed is 10000 rpm, 11000 rpm, 12000 rpm, 13000 rpm, 14000 rpm and 15000 rpm.
[0033] In this embodiment, preferably, the emulsification time is 3, 4, 5, 6, 7, 8, 9 and 10 minutes.
[0034] In this embodiment, the curing method is as follows: adding a curing agent, performing ultrasonic treatment, and then stirring, standing, filtering, and drying.
[0035] In this embodiment, preferably, the solidifying agent is one of maltodextrin, gum arabic, soy protein isolate, modified starch and whey protein concentrate.
[0036] In this embodiment, preferably, the mass fraction of the curing agent is 0.1-1% of the solid content of the mixture.
[0037] In this embodiment, preferably, the ultrasonic intensity is 360W.
[0038] In this embodiment, preferably, the stirring speed is 500 rpm, 1000 rpm or 1500 rpm.
[0039] In this embodiment, preferably, the drying condition is 50° C. and drying for 16 hours.
[0040] In this embodiment, specifically, the mass ratio of the anti-auxiliary agent precipitation encapsulation film is: 100 parts of POE particles; 1-5 parts of microcapsules; 0-0.5 parts of cross-linking agent; 0-0.1 parts of auxiliary cross-linking agent; 0-0.1 parts of light stabilizer; 0-0.1 parts of antioxidant; 0-0.3 parts of silane coupling agent.
[0041] In this embodiment, specifically, in the case where the mass proportion of the cross-linking agent, auxiliary cross-linking agent, light stabilizer, antioxidant and silane coupling agent in the anti-additive precipitation encapsulation film is 0 parts, the additives in the microcapsules are gradually released during the casting and lamination heating to improve the cross-linking degree of the film, etc. After adding a proper amount of additives, the proportion of additives added is much lower than that of the existing POE film formula, which can improve the initial cross-linking performance of the film while reducing the precipitation of additives. Technicians can adjust according to usage requirements.
[0042] In the present embodiment, specifically, in step S2, the microcapsules and POE particles are blended, and the casting film is used to obtain an anti-additive precipitation encapsulation film, which includes: mixing according to a mass ratio, extruding after plasticizing by a screw, and pressing through a roller after flowing out of a die head to form an anti-additive precipitation encapsulation film; wherein the processing temperature is 60-100°C, and under this temperature environment, the low-melting-point polymer wall material releases part of the additive, but the skeleton can be maintained.
[0043] In a second aspect, the present invention further provides an anti-auxiliary agent precipitation encapsulation film obtained by the preparation method as described above, comprising: microcapsules; wherein the microcapsules are prepared by coating the auxiliary agent in an O / W type emulsification manner.
[0044] In a third aspect, the present invention further provides a photovoltaic module, comprising the anti-adjuvant precipitation packaging film as described above.
[0045] In this embodiment, specifically, the processing temperature of the photovoltaic module during the lamination process is 110-180° C., at which the low-melting-point polymer wall material completely melts, and the high-melting-point polymer wall material softens and deforms accordingly, so that the additive can be completely released.
[0046] Initial cross-linking test:
[0047] Sample preparation: After stacking two POE films, take a 50mm×50mm film, and stack the front plate material, non-stick film, film, non-stick mold, and back plate material from bottom to top. Put the front plate into the vacuum laminator with the front plate facing down, and laminate according to the temperature and time required by the product, then take it out and cool it to room temperature for use. After lamination, weigh 0.5g±0.01g and cut it into small particles less than 3mm×3mm. Prepare 3 samples for each group.
[0048] Test method: 1) Wash, dry and weigh the stainless steel mesh bag as W1 (accurate to 0.001g). 2) Put the prepared sample into the stainless steel mesh bag to make a sample package, weigh it as W2 (accurate to 0.001g) 3) Seal the sample package with wire, mark it, insert it from the side of the three-necked flask and seal it with a rubber stopper, add 1 / 2 volume of xylene solvent to the flask, immerse the sample package in the solvent, put a reflux condenser in the middle of the flask, heat it to about 140℃, boil and reflux xylene for 5h, and keep the reflux rate at 20 drops / min to 40 drops / min. 4) After the reflux is completed, take out the sample package and hang it to remove the solvent droplets. 5) Put it in a vacuum oven, control the temperature at 140℃, dry it for 3h, and completely remove the solvent. 6) Take the sample package out of the oven, remove the iron wire, place it in a desiccator to cool for 30 minutes, then take it out and weigh it, recording it as W3 (accurate to 0.001g).
[0049] Result calculation: Calculate the degree of crosslinking according to the following formula, retain two decimal places after the decimal point, and take the average value of the test results.
[0050] D=[(W3-W1) / (W2-W1)]×100%
[0051] Where: D—crosslinking degree, %; W1—mass of empty stainless steel wire mesh bag, g; W2—mass of bag containing sample, g; W3—mass of sample package after solvent extraction and drying, g.
[0052] Crosslinking degree test after heating:
[0053] Add a step of heating the POE sample in an oven at 60°C for 24 hours, and the rest is the same as above.
[0054] Peel force test:
[0055] Sample preparation: 1) Prepare two pieces of POE film raw materials, one piece of glass and one piece of flexible backplane, all of which are 300mm×150mm in size; 2) Stack glass / POE film (two pieces) / flexible backplane in sequence, put them into a vacuum laminator, and laminate them according to the temperature and time required by the product. There should be no bubbles in the POE film in the laminated sample. Prepare 3 samples; 3) Cut the flexible backplane / POE film layer into samples with a width of 10mm±0.5mm every 5mm in the width direction for the peeling force test between POE and glass.
[0056] Test process: According to the test method of GB / T2790-1995, the peeling force F between the glass and the film is measured on a tensile testing machine at a tensile speed of 100mm / min±10mm / min.
[0057] Test results: The peel strength is calculated according to the following formula, and the arithmetic mean of 3 samples is taken, accurate to 0.1N / cm.
[0058] σ=F / B
[0059] Where: σ—180o peel strength, N / cm; F—peel force, N; B—sample width, cm.
[0060] Precipitation test:
[0061] Take a 5g film sample, put it into a 60℃ oven and heat it for 2 hours. Take it out and wipe it with a dust-free cloth to clean the surface. Then weigh it and calculate the lost mass, which is the precipitation amount of the film additive.
[0062] Slip test:
[0063] The film sample was cut into a size of 2 cm × 1 cm, placed in a 60°C oven for 24 hours, and then taken out and placed on frosted glass at an angle of 45°, allowed to slide on its own, and the sliding distance was recorded.
[0064] In addition, optical microscopy was used to observe the morphology of microcapsules, and scanning electron microscopy was used to observe the internal morphology of the film.
[0065] Example 1
[0066] Dissolve 1g of gelatin and 9g of gum arabic in 90g of water to obtain a mixture solution; then add 3.5g of an auxiliary agent into the aqueous solution and perform high shear emulsification at 5000rpm for 10min, raise the temperature to 50°C, adjust the pH value of the system to 3 with acetic acid, coagulate for 60min, cool to 20°C in an ice-water bath, adjust the pH value of the system to 6 with ammonia water, add 0.01g of glutamine transaminase, maintain the temperature and stir to solidify for 2h, let stand, stratify, centrifuge, and dry to obtain microcapsules coated with the auxiliary agent.
[0067]
[0068] The materials are mixed according to the formula, plasticized by the screw, extruded, and flowed out from the die head. The processing temperature is 80°C, and the materials are pressed by rollers to form a packaging film.
[0069] Example 2
[0070] 3 g of gelatin and 7 g of gum arabic were dissolved in 15 g of water to obtain a mixture solution; then 3.5 g of an auxiliary agent was added to the aqueous solution and high shear emulsification was performed at 15000 rpm for 3 min, the temperature was raised to 60°C, the pH value of the system was adjusted to 3 with acetic acid, coagulated for 30 min, cooled to 15°C in an ice water bath, and the pH value of the system was adjusted to 6 with ammonia water, 0.1 g of glutamine transaminase was added, the temperature was maintained and stirred for solidification for 4 h, the mixture was allowed to stand, layered, centrifuged, and dried to obtain microcapsules coated with the auxiliary agent.
[0071]
[0072] The materials are mixed according to the formula, plasticized by the screw, extruded, and flowed out from the die head. The processing temperature is 100°C, and the materials are pressed by rollers to become packaging films.
[0073] Example 3
[0074] 1g chitosan and 9g cyclodextrin were dissolved in 90g water, heated at 70°C to obtain a mixture solution, and kept at a constant temperature; then 2.5g of the auxiliary agent was added to the aqueous solution for high shear emulsification at 10000rpm for 10min, 0.01g of maltodextrin was added, ultrasonicated at 360W for a period of time, then stirred at 500rpm, allowed to stand, filtered, and finally dried at 50°C for 16h to obtain microcapsules coated with the auxiliary agent.
[0075]
[0076]
[0077] The materials are mixed according to the formula, plasticized by the screw, extruded, and flowed out from the die head. The processing temperature is 60°C, and the materials are pressed by rollers to form a packaging film.
[0078] Example 4
[0079] 3g chitosan and 7g cyclodextrin were dissolved in 15g water, heated at 80°C to obtain a mixture solution, and kept at a constant temperature; then 2.5g of the auxiliary agent was added to the aqueous solution for high shear emulsification at 15000rpm for 3min, 0.1g of gum arabic was added, ultrasonicated at 360W for a period of time, then stirred at 1500rpm, allowed to stand, filtered, and finally dried at 50°C for 16h to obtain microcapsules coated with the auxiliary agent.
[0080]
[0081] The materials are mixed according to the formula, plasticized by the screw, extruded, and flowed out from the die head. The processing temperature is 70°C, and the materials are pressed by rollers to form a packaging film.
[0082] Example 5
[0083] 2g of gelatin and 8g of gum arabic were dissolved in 40g of water to obtain a mixture solution; then 3.5g of an auxiliary agent was added to the aqueous solution and high shear emulsification was performed at 12000rpm for 6min, the temperature was raised to 60°C, the pH value of the system was adjusted to 3 with acetic acid, coagulated for 30min, cooled to 15°C in an ice water bath, and the pH value of the system was adjusted to 6 with ammonia water, 0.05g of glutamine transaminase was added, the temperature was maintained and stirred for solidification for 4h, the mixture was allowed to stand, layered, centrifuged, and dried to obtain microcapsules coated with the auxiliary agent.
[0084] POE granules 100 parts;
[0085] Microcapsules 5 parts;
[0086] The materials are mixed according to the formula, plasticized by the screw, extruded, and flowed out from the die head. The processing temperature is 90°C, and the materials are pressed by rollers to form a packaging film.
[0087] Example 6
[0088] 2g chitosan and 8g cyclodextrin were dissolved in 34g water, heated at 80°C to obtain a mixture solution, and kept at a constant temperature; then 2.5g of the auxiliary agent was added to the aqueous solution for high shear emulsification at 12000rpm for 6min, 0.05g of gum arabic was added, ultrasonicated at 360W for a period of time, then stirred at 1000rpm, allowed to stand, filtered, and finally dried at 50°C for 16h to obtain microcapsules coated with the auxiliary agent.
[0089] POE granules 100 parts;
[0090] 3 parts of microcapsules;
[0091] The materials are mixed according to the formula, plasticized by the screw, extruded, and flowed out from the die head. The processing temperature is 100°C, and the materials are pressed by rollers to become packaging films.
[0092] Comparative Example 1
[0093] Comparative Example 1 is relative to Example 1, except that the microcapsules are removed.
[0094]
[0095] Comparative Example 2
[0096] In Comparative Example 2, compared with Example 1, the microcapsules were removed and the auxiliary agent content was doubled.
[0097]
[0098] Comparative Example 3
[0099] Comparative Example 3 is relative to Example 1, except that the content of the auxiliary agent is doubled.
[0100]
[0101] Specifically, the performances of Examples 1-6 and Comparative Examples 1-3 are shown in Table 1.
[0102] Table 1
[0103]
[0104]
[0105] In this embodiment, specifically, the difference between Embodiment 1-4 and Embodiment 5-6 is that Embodiment 1-4 with additional additives has a higher initial crosslinking degree, while Embodiment 5-6 with no additional additives and only using microcapsules obtains a higher peeling force with a lower amount of precipitation.
[0106] In this embodiment, specifically, the formulation with the addition of additives and microcapsules has a higher degree of crosslinking than the formulation with only microcapsules, while in Comparative Examples 1 and 2, because there are no microcapsules, there is precipitation and the degree of crosslinking decreases. It can be seen from the degree of crosslinking after heating that the microcapsule method can well overcome the precipitation problem.
[0107] In this embodiment, specifically, the peeling force of comparative examples 1, 2, and 3 all decreased, and the precipitation of the additive on the surface would cause slippage, reducing the peeling force. The larger the dosage, the more obvious the decrease; at the same time, both the precipitation amount test and the sliding test verified that the microcapsule solution was effective in improving slippage.
[0108] like Figure 1 As shown, in this embodiment, specifically, a small amount of auxiliary agent is released from around the microcapsules after heating at 80° C. for 30 minutes, and it can be clearly seen that the auxiliary agent is completely released after heating at 140° C. for 30 minutes.
[0109] like Figure 2 As shown, a clear microcapsule structure can be seen in the film before lamination, and the microcapsule structure disappears after lamination, while the additive is evenly distributed.
[0110] In summary, the anti-additive precipitation encapsulation film and its preparation method, and the photovoltaic module of the present invention encapsulate the additive in the microcapsule by selecting a high melting point and a low melting point polymer wall material, so that the low melting point polymer wall material releases part of the additive at the casting temperature and can keep the skeleton intact, and at the lamination temperature, the low melting point polymer wall material is completely melted and the high melting point polymer wall material is softened and deformed, so that the additive is completely released without precipitation, thereby effectively achieving the purpose of providing the cross-linking degree of the film.
[0111] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing an anti-adjuvant precipitation encapsulation film, characterized in that: The steps include: Step S1, coating the auxiliary agent required for the film by O / W emulsification to prepare microcapsules; Step S2, blending the microcapsules with the POE particles, and casting the mixture to obtain an anti-additive precipitation encapsulation film; in The O / W type emulsification method of the microcapsule includes: Dissolving the composite polymer wall material in water to prepare an aqueous solution with a mass fraction of 10 to 40 wt%, adding an auxiliary agent to the aqueous solution for high shear emulsification, high-speed dispersion and homogenization emulsification at 5000 to 15000 rpm for 3 to 10 minutes, and curing to obtain the microcapsules; and The composite polymer wall material is a combination of a low-melting-point polymer wall material having a melting point not higher than 100°C and a high-melting-point polymer wall material having a melting point not lower than 110°C; The mass proportion of the anti-additive precipitation encapsulation film is: POE particles 100 parts; 1 to 5 parts of microcapsules; Cross-linking agent 0-0.5 parts; Cross-linking agent 0-0.1 part; Light stabilizer 0-0.1 part; Antioxidant 0-0.1 part; Silane coupling agent 0-0.3 parts.
2. The preparation method according to claim 1, characterized in that The composite polymer wall material is any one of a combination of gelatin and gum arabic, or a combination of chitosan and cyclodextrin.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the low melting point polymer wall material to the high melting point polymer wall material is 1:9 to 3:
7.
4. The preparation method according to claim 1, characterized in that: The solidification is a complex coacervation method.
5. The preparation method according to claim 1, characterized in that: The auxiliary agents include a crosslinking agent, a co-crosslinking agent, a light stabilizer, an antioxidant and a silane coupling agent.
6. The preparation method according to claim 1, characterized in that: In step S2, the microcapsules and POE particles are blended and cast into a film to obtain an anti-additive precipitation encapsulation film, which includes: The materials are mixed according to the mass proportion, extruded after being plasticized by a screw, and pressed by a roller after flowing out of the die to form an anti-adjuvant precipitation encapsulation film; wherein The processing temperature is 60-100℃.
7. An anti-additive precipitation encapsulation film obtained by the preparation method according to any one of claims 1 to 6, characterized in that: include: Microcapsules; in The microcapsules are prepared by coating the auxiliary agent in an O / W emulsification manner.
8. A photovoltaic module, characterized in that: It comprises the anti-auxiliary agent precipitation packaging film as claimed in claim 7.
9. The photovoltaic module according to claim 8, characterized in that: The processing temperature of the photovoltaic module during the lamination process is 110-180°C.
